2014
DOI: 10.1111/acer.12549
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐Related Alcohol Consumption in Heavy Drinkers Correlates with Expression of miR‐10a, miR‐21, and Components of the TARRNA‐Binding Protein‐Associated Complex

Abstract: Background Alterations in stress-related gene-expression may play a role in stress-related drinking and the risk for alcohol dependence. Methods Microarrays were used to measure changes in gene-expression in peripheral blood in non-smoking, social drinking subjects exposed to three types of personalized imagery: neutral, stressful (but not alcohol-related), and alcohol-related cues. Gene-expression was measured at baseline, immediately after, and 1 hour after stimulus presentation. Subjects were allowed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…Other studies examining differences in alcohol preference and alcohol consumption in animal models identified Cacnalg , Kcnh7 , Fgf12 , Gad1 , Luc7l2 , Smpd3 , and Ttn (Carr et al, 2007; Fehr, Rademacher, & Buck, 2003; McClintick et al, 2013; Mulligan et al, 2008; Wang et al, 2014, p. P12). Additionally, seven genes from the RSE vs. NOE or NOE group ( Ankib1 , Astn1 , Ccdc88a , Cpne3 , Tnn , Tns1 , and Synpo2 ) have been shown to be either differentially expressed in human alcoholics versus controls, or identified in a human genome-wide association study on alcoholism (Beech et al, 2014; Gelernter et al, 2014; Kryger & Wilce, 2010; Zuo et al, 2012). Finally, six differentially expressed genes ( Adcy8 , Myef2 , Per3 , S ynpo2 , Tbc1d9b , and Tsc22d3 ) have been linked to both stress and ethanol responses, although separately.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies examining differences in alcohol preference and alcohol consumption in animal models identified Cacnalg , Kcnh7 , Fgf12 , Gad1 , Luc7l2 , Smpd3 , and Ttn (Carr et al, 2007; Fehr, Rademacher, & Buck, 2003; McClintick et al, 2013; Mulligan et al, 2008; Wang et al, 2014, p. P12). Additionally, seven genes from the RSE vs. NOE or NOE group ( Ankib1 , Astn1 , Ccdc88a , Cpne3 , Tnn , Tns1 , and Synpo2 ) have been shown to be either differentially expressed in human alcoholics versus controls, or identified in a human genome-wide association study on alcoholism (Beech et al, 2014; Gelernter et al, 2014; Kryger & Wilce, 2010; Zuo et al, 2012). Finally, six differentially expressed genes ( Adcy8 , Myef2 , Per3 , S ynpo2 , Tbc1d9b , and Tsc22d3 ) have been linked to both stress and ethanol responses, although separately.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-382 in the NAc of mice attenuated excessive alcohol consumption and preference (20%IA2BC paradigm) 155 ; however, more studies are necessary to establish a direct link between endogenous miR-382 and alcohol intake. Furthermore, the levels of miR-10a and miR-21 were elevated in the blood of humans who consumed excessive amounts of alcohol and were exposed to a stressful cue 156 ; it would be of interest to test the role of these specific miRNAs in animal studies.…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…Furthermore, the authors suggested changes in specific gene expressions, which might be related to the upregulation of these miRNAs. As a conclusion of these results, it can be suggested that miR-10a and miR-21 expression in whole blood is regulated by acute psychological stress in this context [22]. …”
Section: Resultsmentioning
confidence: 97%
“…Two of these studies used experimental stress elicitation tasks - analyzing acute, not chronic stress reactions [21,22]. Three of these studies used stressors of everyday life, such as academic exams or tests as events to be expected and therefore functioning as chronic psychological stressors [13,23,24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation